Fabrication and Characterization of Silicalite-1 Membranes for the Separation of the Greenhouse Gases - Carter, David (Université d'Ottawa / University of Ottawa, 2019)
Membranes composed of zeolite crystals, in which gas molecules are transported by surface diffusion, are promising for gas separation applications. Since this mode of mass transfer mechanism is controlled by synergistic adsorption and diffusion phenomena, the separation of gas mixtures is not solely dependent on molecular size. However, undesirable defect pathways in zeolite membranes are often present due to factors such as incomplete crystal growth and/or thermal stresses during membrane synthesis and calcination. These pathways cause molecules to bypass the selective zeolite crystal layer and adversely affect membrane performance. Since the fabrication of defect-free zeolite membranes is very challenging, their widespread adoption for industrial processes has been impeded. Quantification of defects in zeolite membranes is therefore important to improve synthesis protocols of these membranes. In this research, zeolite membranes composed of silicalite crystals have been fabricated using the pore plugging method, and their performance was evaluated by developing a method that can be used to describe the selective and non-selective channels that are present in any zeolite membrane. Unlike the other destructive and sophisticated methods, which already exist to discern this information, the proposed method requires only a limited number of in-situ permeation experiments to be conducted using He – a non-adsorbing gas, and N2 – an adsorbing gas. With this method, the volume fraction, effective length, and size of the selective and non-selective channels of multiple membranes have been quantified, and these parameters were used to predict membrane performance at untested conditions, as well as with untested gases such as CH4 and CO2. In addition, by separating surface diffusion from the flow through the defects in gas separation tests with CO2/N2 mixture, the respective transport diffusivities and exchange diffusivity coefficients, which account for mass transfer in zeolite crystals were determined using the Maxwell-Stefan model. These determined exchange diffusivity coefficients are not equal to each other and challenge the Vignes correlation. In addition, transport diffusivities determined in mixed gas permeation experiments at University of Ottawa have then been validated by large single crystal transport diffusivities for mixed gases that were determined from molecular uptake experiments conducted at University of Leipzig in Germany, using Infra-Red Micro-imaging.
Keywords: Inorganic Membranes; Silicalite; Adsorption; Diffusion; Gas Separations